Monitoring seasonal fine root dynamics of Hevea brasiliensis clone RRIM 600 in Southern Thailand using minirhizotron technique - Sakanan Saelim; Sayan Sdoodee; Rawee Chiarawipa (Songklanakarin Journal of Science and Technology (SJST), 2019)
Rubber tree (Hevea brasiliensis) plantations in various environments are affected by climate variability, and the fine root dynamics of rubber trees significantly respond to environmental factors. Therefore, rubber clone RRIM 600 was used to investigate the fine root dynamics in southern Thailand using minirhizotron imaging at 0-60 cm soil depths from February 2014 to January 2015. Dynamics of fine root production and mortality were greater in the rainy season than in the dry season. The fine root distribution peaked around 20-30 cm and decreased over 40-60 cm soil depths. The maximal leaf area index (April 2014) was found 2 months after leaf flushing, while the fine roots showed a slight increase after leaf development for 1 month (May 2014). Both rainfall and soil moisture had significant (p<0.01) positive correlations with fine roots of which there were more in the rainy season than in the dry season.